Efficacy of a plate model on glycaemic control among individuals with type 2 diabetes mellitus - Tiew, Kee Fong (2015)
Conventional meal planning method helps to improve glycaemic control in individuals with type 2 diabetes mellitus (T2DM) but it also be seen as too complicated and time consuming which results in poor compliance. My Healthy Plate (MHP) is a visual meal planning tool developed to help T2DM patients adhere to the Malaysian Dietary Guidelines, with an emphasis on the use of the plate model concept to represent a balanced diet with the proper portions of food groups that should be consumed at each meal. This quasi-experimental study aimed to determine the effects of MHP on diabetes control in people with T2DM. Subjects were 113 patients with poorly controlled T2DM recruited based on quota sampling, stratified by sex and ethnicity,from the Medical Outpatient Department of Hospital Serdang, Selangor. Subjects were allocated to intervention (n = 55) or control groups (n = 58) to receive either fourlesson MHP program or dietary and diabetes newsletters provided bi-monthly for two months, followed by three-monthly newsletters by mail and telephone call. A total of 84 subjects (intervention = 36, control = 48) completed the assessments at baseline,immediately one- and five-month after the intervention. Overall, none of the baseline characteristics, including socio-demographic, lifestyle habits, diabetes history,psychosocial factors, anthropometric measurements, dietary factors and glycaemic control, were found to be significantly different between intervention and control groups (p > 0.05). Using the 2 x 3 mixed-design ANOVA, the intervention group had greater improvement in total physical activity (interaction effect F = 3.240, p = 0.042),fat-related (F = 3.402, p = 0.036) and fruit and vegetable-related dietary behavior (F = 5.580, p = 0.005), vegetable intake (F = 3.723, p = 0.030), fruit and vegetable intake (F = 5.208, p = 0.008), total food group score (F = 4.754, p = 0.010) and serving score (F = 5.741, p = 0.004) and HbA1c (F = 3.640, p = 0.029) over time than the controls after adjustment for baseline measures. At five-month after intervention, there were significantly higher proportion of intervention subjects who moved to the higher stages of change (χ2 = 14.534, p < 0.0001). Besides, a significant intervention effect was found on perceived barriers to healthy eating (-1.85 points), fruit intake (+0.33 times/day), fruit and vegetable intake (+0.86 times/day), total food group score (+0.46 points) and serving score (+1.51 points) and HbA1c (-1.15%) but not for self-efficacy,physical activity and anthropometric measurements. Multivariate linear regression analysis found that ethnicity, personal income, type of medication, physical activity and perceived barriers were significantly predicted baseline glycaemic control while change in self-efficacy, change in fat-related dietary behavior, change in waist circumference,and treatment allocation significantly predicts change in glycaemic control after adjusted for confounding variables. All intervention subjects were overwhelmingly satisfied with the MHP Program with the majority reported that they understood the program well (91.9%), felt the program was helpful in achieving diet goals (91.9%) and managing diabetes (83.3%). In conclusion, MHP could be an alternative meal planning tool to promote diet quality and glycaemic control among individuals with T2DM.